2021
DOI: 10.1590/fst.03520
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of fenugreek (Trigonella foenum-graecum) seed on type 2 diabetes

Abstract: The hyperglycaemia defines features of type 2 diabetes (T2DM), which is a real time problem and poses a significant economic burden on the globe and is spreading like an epidemic. Currently it affects 384 million people on the globe and this number is expected to reach 592 million in 2035 as reiterated by International Diabetes Federation (IDF). By improving the quality of diet and decreasing the intake of sugary foods T2DM can be treated. Fenugreek seeds powder in sachet form of 20 g/day used to treat type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…ROC curve analysis showed that the correlation between cTnT and CVD was higher than that between NT-proBNP and hsCRP. It also suggested that the increase of cTnT was closely related to the occurrence of CVD (Liu & Li, 2021;Rehman et al, 2021;Yerlikaya et al, 2021). Hill et al (2009) showed that the serum cTnT concentration in MHD patients without acute coronary syndrome was stable within 15 weeks, and the risk of death in MHD patients with increased cTnT was increased.…”
Section: Discussionmentioning
confidence: 99%
“…ROC curve analysis showed that the correlation between cTnT and CVD was higher than that between NT-proBNP and hsCRP. It also suggested that the increase of cTnT was closely related to the occurrence of CVD (Liu & Li, 2021;Rehman et al, 2021;Yerlikaya et al, 2021). Hill et al (2009) showed that the serum cTnT concentration in MHD patients without acute coronary syndrome was stable within 15 weeks, and the risk of death in MHD patients with increased cTnT was increased.…”
Section: Discussionmentioning
confidence: 99%
“…According to Brown & Gordon (2001) ß-glucanhas the same antitumor and antimicrobial stimulatory capabilities as dietary fiber. According to Khan et al (2021), ß-glucan is a soluble fiber and has been shown to reduce blood glucose and cholesterol levels, also supported by research by Rehman et al (2021) that besides that it can also lose weight.…”
Section: Introductionmentioning
confidence: 93%
“…In the in vitro diabetes model induced by high glucose (HG), 5-azacytidine treatment can significantly reduce the expression of DNMT1, and improve the reduction of podocyte slit diaphragm protein caused by hypermethylation (Zhang et al, 2017). At present, the treatment of type 2 diabetes with traditional Chinese medicine has become more and more common (Ahmad et al, 2020). Parthenolide (PN) was originally extracted from the shoots of plant Feverfew, and has strong anti-tumor, anti-inflammatory and antibacterial biological activities (Freund et al, 2020).…”
Section: Introductionmentioning
confidence: 99%